1990
DOI: 10.1016/0012-821x(90)90008-l
|View full text |Cite
|
Sign up to set email alerts
|

Boundary scavenging in the Pacific Ocean: a comparison of10Be and231Pa

Abstract: Concentrations of U, Th, 231pa and 1°Be were measured in Holocene sediments from two cores collected off the west coast of South America, two cores from the East Pacific Rise, two from the equatorial Pacific and one from the south Pacific central gyre. Our results, together with data from 5 cores reported in the literature, show that boundary scavenging plays a major role in the removal of 1°Be from the Pacific Ocean. Deposition rates of 1°Be at three margin sites are more than an order of magnitude greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(92 citation statements)
references
References 66 publications
9
83
0
Order By: Relevance
“…The results of previous studies [9,10] and our work [23][24][25] have shown that l°Be is also preferentially removed from the oceans in some margin areas. In order to evaluate the source of l°Be, and to understand its transport within the oceans, we need to conduct an ocean-wide study: (1) to estimate the extent to which l°Be deposition is enhanced in different ocean margin regions; and (2) to examine what factors influence the scavenging of l°Be from seawater to sediments.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…The results of previous studies [9,10] and our work [23][24][25] have shown that l°Be is also preferentially removed from the oceans in some margin areas. In order to evaluate the source of l°Be, and to understand its transport within the oceans, we need to conduct an ocean-wide study: (1) to estimate the extent to which l°Be deposition is enhanced in different ocean margin regions; and (2) to examine what factors influence the scavenging of l°Be from seawater to sediments.…”
Section: Introductionsupporting
confidence: 65%
“…The initial (i.e., decay corrected) unsupported concentrations of 23°Th and 231pa (des-230 231~ ignated as xs Tho and xs rao, respectively; Table 2), were calculated based methods described previously [23,24]. The basic principle of our approach is to use 23°Th, a nuclide that is produced uniformly throughout the ocean by decay of dissolved 234U and deposited to the sea floor at a rate nearly equal to its production rate in the overlying water column, as a tracer against which 231pa and l°Be are normalized so that 231pa/Ea°Th and l°Be/23°Th ratios in the sediments can be used as indicators of the intensity of scavenging of 231pa and l°Be (see [23] for a description of the normalization and the assumptions implicit therein; and also discussions in Section 3 below).…”
Section: Core Selection and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thorium normalization works on the assumption that the flux of particulate 230 Th sinking to the ocean floor is approximately equal to its known rate of production from 234 U decay in the water column because the residence time of 230 Th in the water column is relatively short (on the order of a few decades) [Anderson et al, 1983b] compared to the timescale for lateral mixing in deep ocean basins [Anderson et al, 1990].…”
Section: Study Area and Methodsmentioning
confidence: 99%